The Effectiveness of Guided Inquiry Learning Model to Improve Science Literacy Skills and Students Self Efficacy on AcidBase Materials - Haniska Virginia Pitaloka; Emmawaty Sofya; Tasviri Efkar (Jurnal Pendidikan dan Pembelajaran Kimia, 2020)
This research was aimed to gain an information about the effectiveness of guided inquiry learning model in improving students' science literacy and self efficacy on acid-base material. This research method is a quasi-experimental with pretest postest control group design. The population in this study were all students of class XI MIA SMA Negeri 3 Metro of the 2019/2020 school year. Sampling on this study are XI MIA 2 as the experimental class and XI MIA 3 as the control class. The effectiveness of guided inquiry learning model was analyzed using the two mean difference test at n-Gain and the effect size test on students' science literacy and self efficacy. The results showed that  guided inquiry learning model had a "large" effect on improving students' science literacy and self efficacy with effect size about 89,01% and 93,28%. The conclusion of this research is the guided inquiry learning model is effective for improving student's science literacy and self efficacy.Keywords: acid-base, science literacy, self efficacy, guided inquiry learning model Penelitian ini bertujuan untuk mendapatkan informasi mengenai efektivitas model pembelajaran inkuiri terbimbing dalam meningkatkan kemampuan literasi sains dan efikasi diri siswa pada materi asam basa. Penelitian ini menggunakan metode kuasi eksperimen dengan pretest-posttest control group design. Populasi yang digunakan yaitu seluruh kelas XI MIA SMAN 3 Metro tahun ajaran 2019/2020. Sampel pada penelitian ini adalah kelas XI MIA 2 sebagai kelas eksperimen dan XI MIA 3 sebagai kelas kontrol. Efektivitas model pembelajaran inkuiri terbimbing di analisis menggunakan uji perbedaan dua rata-rata pada n-Gain dan uji effect size terhadap kemampuan literasi sains dan efikasi diri siswa. Hasil penelitian menunjukkan bahwa model inkuiri terbimbing memiliki pengaruh “besar” dalam meningkatkan kemampuan literasi sains dan efikasi diri siswa dengan effect size sebesar 89,01% dan 93,28%. Pada penelitian ini diperoleh kesimpulan bahwa model pembelajaran inkuiri terbimbing efektif untuk meningkatkan kemampuan literasi sains dan efikasi diri siswa pada materi asam basa.Kata kunci: asam basa, literasi sains, efikasi diri, model pembelajaran inkuiri terbimbing.